PENGUATAN ETIKA PENYELENGGARA NEGARA DALAM PEMBERANTASAN KORUPSI - Hoesein, Zainal Arifin (Al-Qisth Law Review, 2018)
AbstractPower is a depiction of the right to do and not to act which gives birth to certain powers which have the dimension of unity between rights and obligations (rechten en plichten). In relation to the process of governance, rights contain the power to govern themselves (Zelfregelen) and manage themselves (Zelfbesturen), while obligations horizontally mean the power to administer the government properly. Thus, the substance of authority in government is the ability to take legal actions or actions of government. Therefore, every power and authority inherent in every state organizer, the moral and ethical foundation as the basis for the integrity of state administrators must be the main factor in assessing and testing its performance which is realized in the form of respectable policies in the framework of increasing dignity and value fair and civilized humanity for all Indonesian people. Thus, every state organizer must have a strong ethical foundation so that its policy products do not conflict with the constitutional mandate. AbstrakKekuasaan merupakan penggambaran tentang hak untuk berbuat dan tidak berbuat yang melahirkan wewenang tertentu yang berdimensi kesatuan antara hak dan kewajiban (rechten en plichten). Dalam kaitan dengan proses penyelenggaraan pemerintahan, hak mengandung pengertian kekuasaan untuk mengatur sendiri (Zelfregelen) dan mengelola sendiri (Zelfbesturen), sedangkan kewajiban secara horizontal berarti kekuasaan untuk menyelanggarakan pemerintahan sebagaimana mestinya. Dengan demikian, substansi wewenang dalam pemerintahan adalah kemampuan untuk melakukan tindakan atau perbuatan hukum pemerintahan. Oleh karena itu, setiap kekuasaan dan kewenangan yang melekat pada setiap penyelenggara negara, maka landasan moral dan etika sebagai basis integritas penyelenggara negara harus menjadi faktor utama dalam menilai dan menguji kinerjanya yang diwujudkan dalam bentuk kebijakan yang bernilai terhormat dalam kerangka meningkatkan harkat dan martabat serta nilai kemanusiaan yang adil dan beradab bagi seluruh rakyat Indonesia. Dengan demikian, setiap penyelenggara negara harus memiliki landasan etika yang kuat agar produk-produk kebijakannya tidak bertentangan dengan amanat konstitusi.